PERANCANGAN MODEL STRATEGIS TRANSFORMASI BISNIS RADIO LOKAL BERBASIS AI-DRIVEN TECHNOPRENEURSHIP PADA NIRWANA FM BANJARMASIN - Novia Purnamasari; Eddy Soeryanto Soeogoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bachtiar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2026)
The rapid development of Artificial Intelligence (AI) offers strategic opportunities to strengthen technopreneurship models, including within conventional offline businesses. This study aims to design an AI-driven strategic transformation model for a local radio business, focusing on Nirwana FM Banjarmasin, particularly its Event Organizer (EO) services, product sales, and marketing collaborations. A qualitative case study approach was employed, with data collected through in-depth interviews, field observations, and analysis of operational documents to map the existing level of technological integration. The findings reveal a significant digitalization gap, where Nirwana FM has not yet implemented AI in a comprehensive and integrated manner. Operational processes within the EO unit and marketing strategies remain largely manual and rely on fragmented technological tools. To address this issue, the study proposes a strategic AI-based model through the integration of five core solutions: (1) AI-Based Audience Analytics, (2) Predictive Analytics for Product Stock Planning, (3) AI-Powered Social Media Performance Tracking, (4) AI-Assisted Scheduling and Event Management, and (5) Automated Chatbot and Information Services. This model serves not only as an operational optimization framework but also as a sustainable hybrid business transformation strategy for local radio enterprises and MSMEs in the digital era.